Shopping Mall Green Spaces and Customer Revisit Intention: Mediating Effects of Environmental Awareness - Jacob Elli Calderon; Lance Kirby Borlaza; Trisha Mhiey Atendido; Angelica Mae Baldomero; Marcus Kehlie Calces; Raizza Mae Zalavaria; Jayvie Guballo (Journal of Management Studies and Development, 2026)
This study investigated the impact of shopping mall green spaces on customer revisit intention, focusing on the mediating effects of environmental awareness. A causal quantitative design was employed, using purposive sampling to collect data from 300 recurrent visitors to the Mall of Asia Sky Garden via a 5-point Likert scale survey. The data were analyzed using Pearson Correlation and Mediation Regression, with the significance of the indirect effect confirmed by the Sobel Test. Results indicated that all hypothesized relationships were supported, confirming highly significant positive correlations between Green Spaces, Environmental Awareness, and Customer Revisit Intention. The analysis established that Environmental Awareness partially mediated the positive relationship between green space quality and customer revisit intention. The study concluded that while green spaces directly fostered patronage, they also provided a significant psychological pathway by boosting environmental consciousness, which further reinforced customer loyalty.